2012
DOI: 10.1007/s11012-012-9576-8
|View full text |Cite
|
Sign up to set email alerts
|

Flow simulations with multi-particle collision dynamics

Abstract: Multi-particle collision dynamics (MPCD) is a particle based Navier-Stokes solver and in the last ten years it has been largely used to analyze mesoscopic systems where both hydrodynamics and thermal effects have to be taken into account, typical examples being colloidal suspensions and polymer solutions. Though the soundness of this approach is well documented, only a few studies present a systematic validation of the method as a Navier-Stokes solver for relatively complex flows (e.g. unsteady, non-uniform). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…This benchmark problem considers the flow induced by an infinite flat plate, harmonically oscillating in its plane. Previous studies showed that the MPC method is able to simulate the resulting flow for Newtonian fluids [41]. Here, we determine the time-periodic flow profile for ferrofluids and find very good agreement with the prediction for a Newtonian fluid with the corresponding effective, field-dependent viscosity.…”
Section: Introductionsupporting
confidence: 66%
“…This benchmark problem considers the flow induced by an infinite flat plate, harmonically oscillating in its plane. Previous studies showed that the MPC method is able to simulate the resulting flow for Newtonian fluids [41]. Here, we determine the time-periodic flow profile for ferrofluids and find very good agreement with the prediction for a Newtonian fluid with the corresponding effective, field-dependent viscosity.…”
Section: Introductionsupporting
confidence: 66%
“…An example is the multiparticle collision dynamics (MPCD). This method, originally used for systems that include thermal fluctuations, may be used for standard hydrodynamics as well (Angelis et al 2012). Recently, MPCD was used in hydrodynamical applications, see, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In MPCD, the fluid consists of point-like particles, and the Navier-Stokes equation can be derived from the local mass and momentum conservation in the overall ensemble [10]. The mass, velocity and position of the i th point-particle are m i , v i , r i , respectively.…”
Section: Mpcd Implementationmentioning
confidence: 99%
“…Moreover, MPCD can easily include thermal fluctuation and hydrodynamic interaction and be suitable to simulate the complex fluid, such as colloidal particles, polymers or electrolytes. De Angelis [10] verified that MPCD is a particle-based Navier-Stokes solver, and can be employed to simulate typical examples such as colloidal suspensions and polymer solutions. Nowadays, MPCD is extensively employed in many fields, such as soft matter [11,12], biological systems [13,14], colloidal suspensions [8,15,16] and so on.…”
Section: Introductionmentioning
confidence: 99%